Multiple Stereoelectroencephalography-Guided Radiofrequency Thermocoagulations for Polymicrogyria With Startle Seizures: A Case Report - Yi'Ou Liu (Frontiers in Neurology, 2019)
The best results of stereoelectroencephalography (SEEG)-guided radiofrequency thermocoagulation (RF-TC) were observed in epilepsies with more limited lesions, but this procedure is rarely used in a wide range of brain malformation. We report a rare case of polymicrogyria (PMG) combined with drug-resistant startle seizures. Presurgical monitoring was performed using SEEG owing to the large lesion and complexity of PMG. According to the intracranial electrode results, the seizure onset was extensive, with the onset starting earlier in the cingulate sulcus and insular pole than in other sites of the other electrodes. Multi-point and multi-step SEEG-guided RF-TC was used for diffuse lesion and functional protection. RF-TC was first applied to the cingulate sulcus and insular pole, and our patient was rendered free from startle seizures after 2 weeks. Two weeks of observation helped us to observe the efficacy of RF-TC and the changes of SEEG, so as to make the next TC scheme. The patient still had spontaneous seizures after the first treatment. RF-TC was then applied to other sites involved earlier. Finally, the patient reached Engel class IIa for a follow-up period of 1 year. There were no additional startle seizures, and important functional areas were protected.